Analisis Peran Guru dalam Memfasilitasi Perkembangan Kecerdasan Emosional Siswa Kelas XI TKJ 2 di SMK N 1 SUKOHARJO - Septyventia, Dorothea; Budiyanto, Cucuk Wawan; Raharjo, Joko Slamet (Universitas Sebelas Maret, 2024)
ABSTRACT The development of the world of education in Indonesia has adapted to global dynamics and the demands of the increasingly growing world of work. Emotional intelligence (EQ) plays an important role in the holistic development of students, especially at the secondary education level. This research aims to analyze the role of teachers in facilitating the development of emotional intelligence in class XI students through character education. Daniel Goleman suggests that individual success is more influenced by emotional intelligence than intellectual intelligence. A qualitative research approach was used using in-depth interviews and observation as data collection instruments. Research findings show that teachers play a significant role in forming and developing students' emotional intelligence. Teachers are not only teachers, but also role models in showing and teaching students to recognize, understand, manage and develop their emotions positively. In addition, teachers play a role in strengthening character education by integrating values such as honesty, cooperation, responsibility and fortitude in their curriculum. By creating a safe and supportive classroom environment, teachers help students build healthy relationships, increase empathy, and manage conflict well. Keywords: Character Education, Emotional Intelligence, Teacher's Role, Student Empowerment